People pollinating partnerships: harnessing collaborations between botanic gardens and agricultural research organizations on crop diversity - Krishnan, Sarada; Greene, Stephanie L.; Khoury, Colin K.; Kuehny, Jeff; Miller, Allison J.; Moreau, Tara; Novy, Ari (International Society for Horticultural Science, 2020)
The world's botanic gardens are repositories of plant diversity but are seldom considered to be major contributors to conservation and research of crops. Thus, botanic gardens and agricultural research organizations have had somewhat limited interactions historically. An unprecedented three-year collaboration between the American Society of Agronomy, Crop Science Society of America, Soil Science Society of America, the American Public Gardens Association, and the World Food Prize Foundation brought together experts from botanic gardens and the agricultural research community, culminating in a Symposium in April 2019 in Des Moines, Iowa. Funded by a grant from the United States Department of Agriculture – National Institute of Food and Agriculture (USDA – NIFA), one of the major outcomes of this collaboration was the development of a shared Road Map for conservation, use, and public engagement around North America’s crop wild relatives and wild utilized plants – species of interest to both communities. Key takeaways from this collaboration are discussed.